2016
DOI: 10.1016/j.jecp.2016.06.003
|View full text |Cite
|
Sign up to set email alerts
|

The precision of mapping between number words and the approximate number system predicts children’s formal math abilities

Abstract: Children can represent number in at least two ways: by using their non-verbal, intuitive Approximate Number System (ANS), and by using words and symbols to count and represent numbers exactly. Further, by the time they are five years old, children can map between the ANS and number words, as evidenced by their ability to verbally estimate numbers of items without counting. How does the quality of the mapping between approximate and exact numbers relate to children’s math abilities? The role of the ANS-number w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 64 publications
(66 citation statements)
references
References 95 publications
3
58
2
Order By: Relevance
“…Previous studies found that large quantities are likely to be underestimated (Izard & Dehaene, 2008; Krueger, 1982, 1984; Libertus et al., 2016; Odic et al., 2015). We replicate this underestimation bias in the behavioral nonsymbolic number estimation task.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies found that large quantities are likely to be underestimated (Izard & Dehaene, 2008; Krueger, 1982, 1984; Libertus et al., 2016; Odic et al., 2015). We replicate this underestimation bias in the behavioral nonsymbolic number estimation task.…”
Section: Discussionmentioning
confidence: 99%
“…The reference dot quantity either contained 25, 30, or 39 dots, which correspondingly induced overestimation, linear‐like estimation, and underestimation in participants' performance (Izard & Dehaene, 2008). Third, there are individual differences in the underestimation bias in adults (Izard & Dehaene, 2008; Odic et al., 2015) and young children who have acquired symbolic number knowledge (Libertus, Odic, Feigenson, & Halberda, 2016). Altogether, these behavioral findings suggest that people are able to map between the ANS and SNS, but that this mapping is not precise and is subject to a systematic underestimation bias.…”
Section: Introductionmentioning
confidence: 99%
“…Figure shows an example of dot arrays from the Panamath instrument. Developed by Halberda and colleagues, this instrument is widely used by neuropsychologists to index students' ANS acuity for non‐symbolic numerical comparison tasks (e.g., Halberda et al, ; Libertus, Odic, Feigenson, & Halberda, ; Price, Palmer, Battista, & Ansari, ) and has demonstrated inter‐test reliability across other ANS assessments (DeWind & Brannon, ). The Panamath was reliable with a Cronbach's alpha of 0.97 for the sample population.…”
Section: Methodsmentioning
confidence: 99%
“…The Panamath, designed to index students' ANS acuity, was scored for accuracy. While there has been considerable debate about the scoring mechanisms employed for indexing ANS acuity (Libertus et al, ; Price et al, ), Inglis and Gilmore () found that accuracy (the number of correct responses) was an adequate means of indexing the measure. Students earned one point for selecting the color of dots (blue or yellow) that were more numerous and earned zero points for selecting the incorrect color.…”
Section: Methodsmentioning
confidence: 99%
“…Further, according to the mapping account, the ability to translate between ANS and SNS representations would be seen as the progress through which symbolic numerals are being affixed on ANS representations (e.g., Libertus, 2015;Libertus, Odic, Feigenson, & Halberda, 2016). The mapping account would view tasks that involve solely the SNS (e.g., symbolic number comparison) and tasks that invoke both ANS and SNS (e.g., mixed-format comparison) similarlythat is, both tasks would draw on the semantic knowledge afforded by the ANS and performance would be dependent on the quality of the mapping between the SNS and ANS.…”
Section: The Mapping Accountmentioning
confidence: 99%